2011
DOI: 10.1007/s10488-011-0389-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Mental Health Care for Urban, Lower Income Families Referred from Pediatric Primary Care

Abstract: The aim of this study was to evaluate the association of parent-reported barriers on the likelihood of attending a mental health evaluation after referral from pediatric primary care. As the part of procedure, parents of children (N = 55) referred for mental health from primary care completed a 23-item questionnaire (three subscales; Cronbach alpha > 0.7): intangible barriers, tangible barriers, and child functioning. Logistic regression examined associations between responses and referral follow-through. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Some quantitative studies, however, asked more open questions about the reasons for not seeking help or difficulties associated with seeking help/attending services/accessing services. Only two quantitative studies provided data relating to perceived facilitators of accessing mental health services [37, 38]. The amount of relevant quantitative data reported across studies ranged from data relating to responses to a single question [39, 40] or particular questionnaire subscales [23], through studies reporting a breakdown of responses to a large number of questionnaire items [26, 38, 41].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some quantitative studies, however, asked more open questions about the reasons for not seeking help or difficulties associated with seeking help/attending services/accessing services. Only two quantitative studies provided data relating to perceived facilitators of accessing mental health services [37, 38]. The amount of relevant quantitative data reported across studies ranged from data relating to responses to a single question [39, 40] or particular questionnaire subscales [23], through studies reporting a breakdown of responses to a large number of questionnaire items [26, 38, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative studies often asked participants to rate ‘inconvenient (appointment) times’ as a possible barrier, although typically, only a small minority of participants rated this as a barrier [38, 41, 53, 59]. Qualitative studies also identified the cumbersome administrative system [56] and various aspects of the appointment system [44, 45, 57, 61] as perceived barriers/facilitators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a core concept, a PCP's awareness of the barriers to care, and ability to discuss them with families in a sensitive and culturally competent way, increases access by empowering families to engage in their child's mental health care. 63 Yet given limitations on providers' time, the complexity of most local mental health care delivery systems, and the needs of families living in poverty, targeted care coordination may increase successful linkages from primary care to the community. Care coordination, a collaborative and family-centered approach to organizing health care delivery, is considered to be an essential component of the medical home 64,65 that has been effective for children in low-income households.…”
Section: Strategies To Improve Mental Health Access and Outcomes In Pmentioning
confidence: 99%